2014
DOI: 10.1166/jnn.2014.8645
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electromagnetic Properties of Single-Crystalline Fe<SUB>3</SUB>O<SUB>4</SUB> Hollow Nanospheres

Abstract: Magnetite (Fe3O4) hollow nanospheres with an average diameter of 300 nm and an average shell thickness of 40 nm were synthesized by a surfactant-free solvothermal reduction method, and their structure and electromagnetic (EM) properties were investigated. The Fe3O4 hollow nanospheres showed single-crystalline features along the [111] crystal growth direction and a ferrimagnetic behavior at room temperature. The Fe3O4 hollow nanosphere/paraffin composites exhibited a flatter response in the real complex relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…For a sample thickness of thickness of 2.7 mm, the following maximum RL values were observed: −14.9 dB for U0 at 12.5 GHz, −49.2 dB for U1 at 11.9 GHz, and −35.1 dB, and −29.1 dB for U2 and U4, respectively, at 12.8, and 12.1 GHz (Figure (a–d), respectively). Previous studies have noted a link between the excellent EMW absorption performance of porous samples and their unique morphologies (e.g., flower‐like), in terms of effective permittivity and impedance matching . The present porous Fe 3 O 4 nanospheres showed strong absorption and a thin coating thickness compared with previous reports (Table ).…”
Section: Resultssupporting
confidence: 54%
“…For a sample thickness of thickness of 2.7 mm, the following maximum RL values were observed: −14.9 dB for U0 at 12.5 GHz, −49.2 dB for U1 at 11.9 GHz, and −35.1 dB, and −29.1 dB for U2 and U4, respectively, at 12.8, and 12.1 GHz (Figure (a–d), respectively). Previous studies have noted a link between the excellent EMW absorption performance of porous samples and their unique morphologies (e.g., flower‐like), in terms of effective permittivity and impedance matching . The present porous Fe 3 O 4 nanospheres showed strong absorption and a thin coating thickness compared with previous reports (Table ).…”
Section: Resultssupporting
confidence: 54%
“…In this study, μ r ″ showed a resonance peak at ∼4 GHz and assumed a negative value up to −0.03 in the frequency range of 17.2–18 GHz owing to the dissipation of electromagnetic wave energy in the cavity of the hollow nanospheres. Similarly, a μ r ″ value of −0.41 has been reported in the frequency range of 12.96–16.56 GHz for porous Fe 3 O 4 /SnO 2 core/shell nanorod based wax composites . A negative value of ε r ″ in some frequency ranges may be because of the formation of continuous conductive network of CNFs inside the polydimethylsiloxane polymer matrix.…”
Section: Resultsmentioning
confidence: 78%
“…Hence, the in situ emerged CO 2 bubbles played a key role in the formation of the hollow structures, which was essential for the inside-out Ostwald ripening and accelerated the hollowing process distinctly. Without the assistance of gas bubbles, only solid microspheres were obtained even under prolonged reaction times of 30 h. [8,12] This confirmed the determining role of the bubbles in the formation of the hollow structures.…”
Section: Resultsmentioning
confidence: 58%
“…[5][6][7][8][9][10][11][12] In those previous studies, though magnetite hollow spheres with a narrow diameter distribution have been successfully synthesized, the diameter and shell thickness of the spheres could not be tuned conveniently. In the solvothermal process, an alkaline substance, such as NaOH, was added to the system to supply OH À [6][7][8][9] because Fe 3þ could not be reduced by ethylene glycol in the absence of OH À .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation